2017
DOI: 10.4028/www.scientific.net/kem.734.37
|View full text |Cite
|
Sign up to set email alerts
|

The High Temperature Creep Properties of a Thermally Sprayed CoNiCrAlY Coating via Small Punch Creep Testing

Abstract: Thermal barrier coatings (TBC’s) protect superalloy components from excessively high temperatures in gas turbines. TBC’s comprise of a ceramic top coat, a metallic bond coat and a thermally grown oxide (TGO). The creep behaviour of the MCrAlY bond coat, which is sensitive to the composition and the method of deposition, has a significant effect on the life of the TBC. High velocity oxy-fuel (HVOF) thermal spraying is a popular deposition method for MCrAlY bond coats however the creep properties of HVOF MCrAlY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Soltysiak et al reported a study on using SPT to characterise a thermally sprayed IN625 coating [33]. Chen et al applied SPT to evaluate the ductile-to-brittle transition and creep behaviour of CoNiCrAlY coatings [34][35][36]. These are the limited studies available on using the SPT for coatings, which have demonstrated the importance and suitability of using the SPT for mechanical characterisation of thermally sprayed coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Soltysiak et al reported a study on using SPT to characterise a thermally sprayed IN625 coating [33]. Chen et al applied SPT to evaluate the ductile-to-brittle transition and creep behaviour of CoNiCrAlY coatings [34][35][36]. These are the limited studies available on using the SPT for coatings, which have demonstrated the importance and suitability of using the SPT for mechanical characterisation of thermally sprayed coatings.…”
Section: Introductionmentioning
confidence: 99%
“…A specific European action related to the standard concerns modelling and analysis, which is to be covered in the paper by Abendroth Small Sample Test Technique [37] in this conference. Other European work on SP creep testing which may later be considered for incorporation into the SP creep standard is presented also by other authors namely for very high temperatures (Jackson et al [38], Dymacek et al [39] and Jeffs et al [40]), for ring specimens (Hyde [41]) and for fatigue loading (Lancaster et al [42]) On the other hand the JRC have chosen to show their results [44] using the Wilshire equations [45,46] deriving F/Fmax for Small Punch tests as described in [47] Their results are compared to NIMS uniaxial data in Figure 19 where the difference in the SP and uniaxial results can be eventually related to the k SP in the equation relating SP load and stress given in the Code of Practice, namely…”
mentioning
confidence: 99%